THE EFFECT OF WORKING CAPITAL MANAGEMENT ON THE PROFITABILITY OF SMALL AND MEDIUM ENTERPRISES: META-ANALYSIS - Supiyadi, Dedi (Universitas Indonesia Membangun (Inaba), 2023)
The relatively small amount of literature related to working capital management (WCM) has contributed to some issues relevant to WCM literature, including a lack of inter-country research. The primary aim of this study was to review research on the impact of WCM on SMEs’ profitability to help researchers specify gaps in the literature and direct research efforts considering how WCM has attracted research attention, especially after the financial crisis in 2008. This paper has been carried out by adopting the SLR methodology. To the best authors’ knowledge, the inter-country review regarding the topic has been almost nonexistent to date. The review has concluded that there is a negative relation between WCM and SMEs’ profitability. Complete discussion can be concluded that further researchers can provide more empirical evidence from other countries to support the finding.